Settler Colonialism and Cultural Studies: Ongoing Settlement, Cultural Production, and Resistance. (February 2017) - Rowe, Aimee Carrillo; Tuck, Eve
In this editorial, we consider what is at work in a turn toward analyzing settler colonialism, and what this turn makes available in cultural studies and discussions of cultural production. Recent theorizations of settler colonialism reveal how cultural productions remain complicit with ongoing settlement, both in everyday practices and intellectual projects like queer studies, feminist studies, and critical race studies. This special issue considers the political stakes of the complicity of cultural studies in settler colonialism, Indigenous erasure, and anti-Blackness, and expands, revises, and repurposes the scope of the field's inquiry, politics, and archive.